2019
DOI: 10.1002/ajmg.b.32777
|View full text |Cite
|
Sign up to set email alerts
|

Genetic meta‐analysis of obsessive–compulsive disorder and self‐report compulsive symptoms

Abstract: We investigated whether obsessive-compulsive (OC) symptoms from a populationbased sample could be analyzed to detect genetic variants influencing obsessivecompulsive disorder (OCD). We performed a genome-wide association studies (GWAS) on the obsession (rumination and impulsions) and compulsion (checking, washing, and ordering/precision) subscales of an abbreviated version of the Padua Inventory (N = 8,267 with genome-wide genotyping and phenotyping). The compulsion subscale showed a substantial and significan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 40 publications
5
27
1
Order By: Relevance
“…In line with the findings of an earlier GWAS of obsessive-compulsive symptoms 35 , a recent meta-analysis of the PGC-OCD GWAS and a GWAS of compulsive symptoms in 8,267 nonclinical subjects revealed the most significant enrichment for genes expressed in brain regions associated with the neurocircuitry of OCD, i.e. the cingulate cortex, nucleus accumbens, and amygdala 36 . Taken together, the aforementioned GWASs suggest a role for synaptic, neurodevelopmental, and immune processes in the etiology of OCD.…”
Section: Genome Variantssupporting
confidence: 65%
See 1 more Smart Citation
“…In line with the findings of an earlier GWAS of obsessive-compulsive symptoms 35 , a recent meta-analysis of the PGC-OCD GWAS and a GWAS of compulsive symptoms in 8,267 nonclinical subjects revealed the most significant enrichment for genes expressed in brain regions associated with the neurocircuitry of OCD, i.e. the cingulate cortex, nucleus accumbens, and amygdala 36 . Taken together, the aforementioned GWASs suggest a role for synaptic, neurodevelopmental, and immune processes in the etiology of OCD.…”
Section: Genome Variantssupporting
confidence: 65%
“… The GeneNets algorithm was used to ascertain whether a set of obsessive-compulsive disorder (OCD) risk genes were more significantly connected to each other in a functional network as would be expected by chance alone. Accordingly, a total of 204 OCD-associated genes were selected from studies cited throughout the present review (more specifically, seven genome-wide association studies [GWASs] 29 31 , 35 , 36 , 41 , 42 , two whole-exome sequencing [WES] studies 45 , 46 , two copy number variant [CNV] studies 58 , 59 , and one functional variants study 100 ) for the GeneNets exploratory analysis. A total of 125 of these genes were included in a significant network, in which three communities were enriched for biological pathways.…”
Section: Ocd Genetic Architecture: An Exploratory Modelmentioning
confidence: 99%
“…To evaluate the genetic risk for obsessive-compulsive disorder and lifetime use of cannabis, polygenic risk scores (PRS) were calculated, using summary statistics for cannabis dependence ( 23 ) and the scores reported by the Psychiatric Genomic Consortium for obsessive-compulsive disorder ( 8 ). Polymorphisms were selected with p -values < 0.05, as reported in the summary statistics, which had good genotyping quality control.…”
Section: Methodsmentioning
confidence: 99%
“…OCD is a symptomatological spectrum, which has made it difficult to clarify its etiology, but there are some known risk factors, including a genetic factor and alterations in neurotransmitters and brain function (7). Genes have recently been discovered that may play an important role in the alteration of glutamatergic signaling (8), and OCD is one of the mental disorders most accompanied by alterations in brain function, mainly in the cortical-striatalthalamic circuit (9)(10)(11). Alterations have also been reported in the levels of neurotransmitters such as serotonin, dopamine, and glutamate (7).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with its genetic underpinnings [11], several family studies have demonstrated that first-degree relatives (FDRs) of individuals with OCD are at an increased risk for developing the disorder [12,13]. In addition, diverse genetic approaches have indicated that subclinical OCD and the full-blown disorder share a considerably similar genetic predisposition [14,15]. Since subclinical OCD can portend the full-blown disorder in children and adolescents, especially those with greater genetic susceptibility [16], the discovery of markers of vulnerability to OCD in this high-risk population could lead to the development of novel approaches for early detection and management of susceptibility to OCD in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%